Prognostic Value of Neutrophil–Lymphocyte Ratio, Platelet–Lymphocyte Ratio, and Combined Neutrophil–Lymphocyte Ratio and Platelet–Lymphocyte Ratio in Stage IV Advanced Gastric Cancer - Wang, Huan; Ding, Yongfeng; Li, Ning; Wu, Luntao; Gao, Yuan; Xiao, Cheng; Jiang, Haiping; Zheng, Yulong; Mao, Chenyu; Deng, Jing; Wang, Haiyong; Xu, Nong (Frontiers in Oncology, 2020)
Background: The prognostic value of neutrophil–lymphocyte ratio (NLR), platelet–lymphocyte ratio, and the combined NLR–PLR score in patients with stage IV gastric carcinoma (GC) has not yet been clarified. Therefore, this study aimed to explore the potential association of NLR, PLR, and NLR–PLR score with the prognosis of patients with stage IV GC. Methods: This retrospective study included 466 patients with GC diagnosed between 2010 and 2017. High NLR and high PLR were defined using the median values as the cutoff values. We then combined the NLR and PLR value and generated the NLR–PLR score as a new biomarker. Patients were divided into three groups according to their NLR–PLR score. Univariate and multivariate analyses were conducted to compare survival outcomes. Results: Median overall survival (OS) and progression-free survival (PFS) were 15.5 months (range, 0.7–96.8 months) and 6.7 months (range, 0.5–30.4 months), respectively. The NLR, PLR, and the NLR–PLR scores were correlated with clinical outcomes such as OS and PFS. Median OS for patients with NLR–PLR scores of 0, 1, and 2 was 22.5, 15.7, and 11.2 months, respectively. Median PFS for patients with these NLR–PLR scores of 0, 1, and 2 was 7.8, 7.1, and 5.2 months, respectively (P < 0.001). High NLR–PLR scores predicted poor survival in patients with stage IV GC (all P < 0.05). Conclusion: Our findings provide scientific evidence to support that the NLR–PLR score may be able to independently predict survival outcomes in patients with stage IV GC.